Pengaruh Return On Asset (ROA), Net Profit Margin (NPM),Firm Size Dan Leverage Terhadap Deviden Payout Ratio Pada Perusahaan Indeks LQ 45 Yang Terdapat Di Bursa Efek Indonesia - Winda Putri Dwita Br Lubis; Nina Purnasari; Rahel Angelina Simalango; Sondang Aida Silalahi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the effect of ROA (Return on Assets), NPM (Net Profit Margin), Firm Size, Leverage on Dividend Payout Ratio in LQ 45 Index companies on the Indonesia Stock Exchange for the period 2019-2022. Sampling in this study using purposive sampling technique with a total sample of 18 companies. The analysis methods used in this study are descriptive statistics, classical assumption tests including normality tests, multicollinearity tests, autocorrelation tests, heteroscedasticity tests, and hypothesis testing including multiple linear regression analysis, coefficient of determination, f test and t test. In testing the hypothesis in this study, there are partial and simultaneous results. The results partially show that the variable net profit margin has a positive and significant effect on the dividend payout ratio, and return on assets, firm size, leverage has a negative and significant effect on the dividend payout ratio. While the results simultaneously show that the variable return on assets, net profit margin, firm size, and leverage affect the dividend payout ratio in the LQ 45 Index Company Located on the Indonesia Stock Exchange. Keywords: Roa (Return On Assets), Npm (Net Profit Margin), Firm Size, Leverage, Dpr (Dividend Payout Ratio)